Comparison of Clinical Characteristics and Prognosis Among Spontaneous Pneumothorax Patients of Different Ages: A Two-Year Follow-Up Study - Wang T; Bai Y (International Journal of General Medicine)
Ting Wang,1 Yang Bai2 1Department of Respiratory Medicine, Xi’an People’s Hospital (Xi’an No.4 hospital), Xi’an, 710004, People’s Republic of China; 2Department of Medical Ultrasonics, Xi’an People’s Hospital (Xi’an No.4 hospital), Xi’an, 710004, People’s Republic of ChinaCorrespondence: Yang Bai, Department of Medical Ultrasonics, Xi’an People’s Hospital (Xi’an No.4 hospital), Xi’an, 710004, People’s Republic of China, Tel/Fax +86-18220874065, Email 49876597@qq.comPurpose: Spontaneous pneumothorax (SP), which is usually characterized by sudden chest pain and shortness of breath, can occur at any age. In this study, patients with SP across various age groups were enrolled, and their clinical features and prognoses were compared.Patients and Methods: The patients were divided into three groups: neonates (n=52), adolescents/adults (n=76), and elderly (n=70). All patients were followed up for two years. The patients’ clinical characteristics, treatments, laboratory indicators on admission, and symptoms over two years were collected and compared. Additionally, as most patients in the elderly group had chronic obstructive pulmonary disease (COPD), data about patients’ lung function tests and medication were also analyzed.Results: Compared with adolescents/adults (6.45± 0.24 days), patients with SP in the neonate and elderly groups had more comorbidities, resulting in a longer hospital stay (13.85± 0.34 days in neonates and 9.50± 0.36 days in the elderly). The main comorbidities in the latter two groups were neonatal asphyxia (17/52) and COPD (48/70), respectively. During the two-year follow-up period, elderly patients with SP had more long-term respiratory symptoms, including coughing, expectoration, and dyspnea, than those in the other two groups. Analysis of the main subgroup (48 COPD cases) in the elderly group revealed that, in the two years after the occurrence of pneumothorax, acute exacerbation times increased; group E cases/(A+B) cases were 4/44, 4/44, 5/43, and 7/41 every 6 months respectively. Additionally, lung function indexes (FEV1, FVC, MEF25,50,75) decreased.Conclusion: Compared to adolescents and adults, newborn and elderly patients with SP are more prone to comorbid lung diseases and longer hospitalization times. The prognosis of neonates is significantly better than the other groups. Increased frequency of acute exacerbations and a deteriorating trend in pulmonary function were observed in patients with COPD after discharge.Keywords: spontaneous pneumothorax, neonate, adolescent, elderly, prognosis